IMPLEMENTATION OF A QUALITY MANAGEMENT SYSTEM BASED ON HACCP IN RESTAURANTS AND CAFÉS: IMPROVING SAFETY AND SERVICE QUALITY (International journal of artificial intelligence, 2026)
The article examines the implementation of a quality management system based on HACCP (Hazard Analysis and Critical Control Points) in restaurants and cafés. The main principles of HACCP, stages of its implementation, and its impact on food safety and service quality are analyzed. Special attention is paid to modern sanitary requirements, control of food preparation processes, and reduction of food poisoning risks. The practical significance of the study lies in the development of recommendations for optimizing quality management processes in the public catering sector.